Pengaruh Tegangan Eksitasi Terhadap output Tegangan Generator Sinkron 3 Fasa 6,3kV - Prastyono Eko Pambudi; Muhammad Suyanto*; Dio Septa Yogaswara (Jurnal Teknologi, 2022)
Synchronous generators work by changing mechanical energy into 1 and 3 phase electrical energy. Reactive power is needed by consumers to generate magnetic fields in inductive electrical loads. The reactive power setting can be adjusted by increasing or decreasing the excitation current. Excitation current is a DC electric current that is supplied to the generator rotor to generate a magnetic field. The excitation current is proportional to the reactive power released by the generator. This is indicated by the increase in the reactive power of the generator which was initially valued at 0.6999 MVAR to 0.7655VAR after the excitation current was increased from 0.130 kA to 0.140 kA. The data used is measurement data per day from July 1 to July 14, 2022. Calculation of reactive power using the power triangle formula has results that are close to the values of reactive power measured by the largest difference of 0.0198 MVAR or 2.8637547%. The reactive power is all positive so the state of the generator is lagging. The output voltage tends to be stable near the nominal voltage of 6.3 kV, this is because the increase and decrease in excitation is intended to keep the generator output voltage stable.